Análisis Exploratorio de Algunas Características Epidemiológicas del Tumor Phyllodes, Hospital Edgardo Rebagliatti Martins Perú (1989-1995) - Assayag, Moisés (1997)
Phyllodes tumor (Giant Intracanalicular Fibroadenoma) is a breast neoplasm. It shows an enhanced incidence in some countries during the last years. We aim to make an exploratory study of Phyllodes tumor’s epidemiologic features, based in 53 cases from Hospital Nacional Edgardo Rebagliati Martins (HNERM), Lima, between 1989 to 1995. Their mean age was 43,45 years. 67,9% were pre-menopausal women. 39,6% were from Lima and 69,8% of them were living there during diagnosis time. Histologically, most cases (81,13%) were benign. The malignant type were the less frequent. This was seen in patients who were 30 or more years old. These findings showed that the greater the number of pregnancies, the less the frequency of the tumor. Moreover, there is no evidence of high laboral or industrial exposition to cancerigenic agents. Migration to Lima (an urban zone) was associated with tumor among youngest people. We think that some different gyneco-obstetrics factors play a role in the spreading of this tumor.